1----3----8----19----42----89 ? ------- Series

---2----5----11----23----47 -------- Difference between the terms

In this series the difference between the 2nd and 3rd terms

( 2nd difference ) is

2nd term + 1st difference - 0th difference

ie., = 3 + 2 + NA (0) = 5.

Now similarly 3rd difference is

3rd term + 2nd difference - ( all previous differences )

= 8 + 5 - 2 = 11.

Finally by this analogy we have the final difference

= 89 + 47 - ( 2 + 5 + 11 + 23). = 95.

So the final term will be 89 + 95 = 184.